A heat dissipation graphite material for LED large-screen display and preparation method thereof
By introducing modified nanocarbon fibers and modified sodium alginate into the graphite heat dissipation film, a tight heat conduction path is formed, which solves the problem of layering and powder loss during the pressing process of graphite heat dissipation film, and achieves efficient heat dissipation and mechanical strength improvement, and is suitable for the heat dissipation system displayed by large LED screens.
Patent Information
- Application Number
- CN202411458260.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-18
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2044-10-18
AI Technical Summary
The existing graphite heat dissipation films are prone to layering and edge powder loss during the pressing process, which makes it difficult to form.
The heat dissipation graphite material including a graphene layer is used. The graphene layer is composed of graphite powder, nanosilver, modified nanocarbon fibers, modified sodium alginate, sodium carboxymethylcellulose, thermal conductivity and plasticizer. Through the bonding of the modified nanocarbon fibers and modified sodium alginate, a tight heat conduction path is formed to improve the thermal conductivity and mechanical strength of the material.
It effectively improves the thermal conductivity and mechanical strength of heat dissipation graphite materials, reduces layering and powder loss, improves the uniformity and stability of molding, and meets the high requirements for heat dissipation performance of LED large-screen displays.
Smart Images

Figure GDA0005263509260000091
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of thermally conductive and heat dissipating materials, and more specifically, to a heat dissipating graphite material for LED large-screen displays and a preparation method thereof. Background Art
[0002] LED is widely used in various lighting equipment due to its low power consumption, long life, easy control and impact resistance. LED also has the characteristics of no flicker, fast startup, energy saving and environmental protection, and is regarded as a new generation of ideal light source by the optoelectronics industry.
[0003] LED displays generate a lot of heat when working. If the heat is not dissipated in time, the brightness of the display will decrease, the life span will be shortened, and even malfunctions will occur. Graphite heat sinks or films made of graphite materials are usually attached to LED chips or back panels. The high thermal conductivity of graphite materials can quickly transfer heat from the LED chip to the heat sink, effectively reducing the temperature of the display and preventing brightness reduction and shortened life due to overheating.
[0004] In the prior art, during the pressing process of the graphite heat dissipation film, the graphite particles are prone to delamination and edge powdering, which makes molding difficult. Summary of the invention
[0005] In order to improve the problem of easy delamination and edge powder loss of graphite heat dissipation film during the pressing process, the present application provides a heat dissipation graphite material for LED large-screen display and a preparation method thereof.
[0006] In the first aspect, the present application provides a heat dissipation graphite material for LED large-screen display, which adopts the following technical solution:
[0007] A heat dissipating graphite material for LED large-screen display comprises a graphene layer and a thin film coating. The graphene layer comprises the following raw materials: 50-60 parts of graphite powder, 1-2 parts of nano silver, 25-30 parts of modified nano carbon fiber, 10-15 parts of modified sodium alginate, 3-6 parts of sodium carboxymethyl cellulose, 5-8 parts of thermal conductor and 3-5 parts of plasticizer.
[0008] By adopting the above technical solution, the graphite powder has high thermal conductivity, which can effectively improve the thermal conductivity of the heat dissipation graphite material, accelerate the transfer of heat, and thus improve the heat dissipation efficiency. The graphite powder has good chemical stability, mechanical strength and toughness, and the obtained heat dissipation graphite material has better comprehensive performance. Nanosilver has extremely high thermal conductivity and can be filled between graphite sheets to form a good heat conduction path, enhance the thermal conductivity between graphite sheets, improve the thermal conductivity of the heat dissipation graphite material, accelerate the transfer of heat, thereby improving the heat dissipation efficiency, and can also improve the mechanical properties of the graphite material, such as improving strength and toughness.
[0009] The modified nanocarbon fiber has high thermal conductivity and can be dispersed in the graphite powder structure, adsorbing graphite powder and nanosilver, so that the graphite powder, nanosilver and modified nanocarbon fiber are closely connected, forming a good heat conduction path, improving the thermal conductivity of the graphite material, and thus enhancing the heat dissipation effect. In addition, the high strength characteristics of the modified nanocarbon fiber enhance the mechanical strength of the graphite material, making it less susceptible to damage when subjected to external forces, and suitable for heat dissipation applications that require high mechanical stability. The modified sodium alginate has a certain viscosity, which makes the graphite powder, nanosilver and modified nanocarbon fiber bond tightly to form a stable structure.
[0010] Sodium carboxymethyl cellulose is used as a dispersant to evenly disperse graphite particles, nanosilver and modified nanocarbon fibers, enhance the adhesion and stability of graphite materials, avoid cracking or deformation of materials, improve the plasticity and extrudability of materials, and facilitate subsequent processing and molding; thermal conductors further assist graphite powders to improve the thermal conductivity of graphite materials, so that heat can be conducted more quickly and evenly inside the material, thereby improving heat dissipation efficiency; plasticizers can improve the fluidity of materials, making them more uniform during mixing and dispersion, avoiding agglomeration and stratification, and improving the uniformity and stability of materials; they can reduce the brittleness of graphite materials, improve their flexibility and impact resistance, make them less likely to break when subjected to external forces, and improve the durability and reliability of materials; they can reduce the melting point and viscosity of graphite materials, making them more plastic at lower temperatures, and facilitating the processing and molding of materials.
[0011] Optionally, the mass ratio of the graphite powder, the modified carbon nanofiber and the modified sodium alginate is 4-5:2-2.5:1.
[0012] By adopting the above technical scheme, the mass ratio of graphite powder, modified nanocarbon fiber and modified sodium alginate is further limited within a certain range, the combination of each raw material component has better comprehensive performance, the modified nanocarbon fiber can be dispersed in the graphite powder structure, the modified sodium alginate makes the graphite powder, nanosilver and modified nanocarbon fiber tightly connected, the graphite powder, modified nanocarbon fiber and modified sodium alginate have a synergistic effect, forming a good heat conduction path, improving the thermal conductivity of the graphite material, and thus enhancing the heat dissipation effect.
[0013] Optionally, the method for preparing the modified carbon nanofiber comprises the following steps:
[0014] (1) dispersing carbon nanofibers in a sulfuric acid solution, soaking at 80-83° C. for 2-3 h, washing with water, and then mixing with ethanol and ball milling to obtain pretreated carbon nanofibers;
[0015] (2) dispersing the carbon nanofibers pretreated in step (1) in deionized water, adding nano-nickel, and stirring to obtain a mixed solution;
[0016] (3) Spraying the acetic acid solution of chitosan on the surface of graphene, drying, then adding it to the mixed solution of step (2), stirring evenly, filtering, and drying to obtain modified nano-carbon fibers.
[0017] By adopting the above technical scheme, sulfuric acid is used to activate the surface of the nanocarbon fiber, and impurities and oxide layers on the surface of the carbon fiber are removed through chemical reaction, thereby improving its surface activity, increasing the roughness of the surface of the nanocarbon fiber, and forming a tiny concave-convex structure, which helps to improve the mixing of the carbon fiber with other materials; after mixing with ethanol and ball milling, the pretreated nanocarbon fiber obtained has a higher surface activity, thereby improving the interfacial bonding force between the nanocarbon fiber and other materials, thereby improving the performance of the nanocarbon fiber.
[0018] Nano-nickel has high electrical conductivity and thermal conductivity. Nano-nickel is loaded in the pore structure and surface of nano-carbon fibers, which significantly improves the electrical conductivity and thermal conductivity of the material. It can also enhance the mechanical properties of nano-carbon fibers, such as strength and toughness. In subsequent applications in graphite materials, it can improve the thermal conductivity of graphite materials. It can also improve the processing performance of graphite materials, improve the plasticity and extrudability of graphite materials, and facilitate subsequent processing and molding.
[0019] Graphene has extremely high thermal conductivity, mechanical strength and folding resistance. Chitosan coats graphene to increase the mechanical properties of graphene, allowing graphene to be stably loaded on the surface of nano-carbon fibers. Chitosan is sticky, allowing graphene and nano-carbon fibers to adhere tightly, increasing the thermal conductivity and mechanical strength of nano-carbon fibers. During the early mixing process of graphite materials, each component is mixed evenly to ensure the density and uniformity of the material.
[0020] Chitosan acts as a binder and evaporates during the subsequent baking process of the graphite material. The graphite particles will be rearranged, making the graphene and nano-carbon fibers densely mixed to form a tighter structure, thereby improving the thermal conductivity of the material.
[0021] Optionally, the mass ratio of the acetic acid solution of the nano-carbon fiber, nano-nickel, graphene and chitosan is 1g:0.2-0.5g:25-30mg:0.3-0.5mL.
[0022] By adopting the above technical scheme, the mass ratio of the ethanol solution of nanocarbon fibers, nano-nickel, graphene and chitosan is further limited within a certain range, and the obtained modified nanocarbon fibers have high thermal conductivity and mechanical properties. Nano-nickel is loaded in the pore structure and surface of the nanocarbon fibers, and chitosan is coated with graphene, so that the graphene is stably loaded on the surface of the nanocarbon fibers. Chitosan is sticky, so that the graphene and nanocarbon fibers are tightly bonded, and at the same time, the structure of the nanocarbon fibers, nano-nickel and graphene is dense, which can be subsequently mixed with other components to improve the corresponding performance of the graphite material.
[0023] Optionally, the preparation method of the modified sodium alginate comprises the following steps:
[0024] (1) dispersing sodium alginate in deionized water, adjusting the pH value to 8-9, adding triethylenediamine and toluene diisocyanate, stirring at a temperature of 70-75° C. for 0.5-1 h to obtain a cross-linked modified sodium alginate solution, adding ethanol, filtering, and drying to obtain sodium alginate powder;
[0025] (2) Dispersing the sodium alginate powder of step (2) in deionized water, adding polyvinyl alcohol, silane coupling agent and copper powder, stirring evenly, drying and grinding to obtain modified sodium alginate.
[0026] By adopting the above technical scheme, sodium alginate and toluene diisocyanate TDI undergo a cross-linking reaction to obtain cross-linked modified sodium alginate, and triethylenediamine is used as a catalyst to enable the cross-linking reaction to proceed effectively, thereby improving the efficiency of the cross-linking reaction. The cross-linked modified sodium alginate has good mechanical properties and is added to graphite materials to improve the mechanical properties of the graphite materials.
[0027] Polyvinyl alcohol has good film-forming and adhesion properties, while cross-linked sodium alginate has biocompatibility and gel-forming ability. The mixture of the two enhances the mechanical properties of the composite material, such as improving strength and toughness, while maintaining good biocompatibility. Silane coupling agents promote the interface bonding of polyethylene mixed with cross-linked sodium alginate, improve the compatibility and bonding strength of the composite material, and improve the tensile strength, elastic modulus and toughness of the material, which will subsequently help improve the corresponding properties of the graphite material, help to evenly mix the components of the graphite material, and help to press into a film.
[0028] Copper powder has excellent electrical conductivity and high thermal conductivity. It can be inserted into the structure of sodium alginate to improve the electrical conductivity, heat dissipation, mechanical strength and toughness of the system. During the graphitization process, copper powder can act as a catalyst to promote the orderly arrangement of carbon atoms, increase the crystallinity and degree of graphitization of graphite materials, and thus improve the thermal stability and thermal conductivity of graphite materials.
[0029] Optionally, the mass ratio of the sodium alginate, polyvinyl alcohol and silane coupling agent is 1:0.5-0.8:0.1-0.2.
[0030] By adopting the above technical scheme, the mass ratio of sodium alginate, polyvinyl alcohol and silane coupling agent is further limited within a certain range, and the obtained sodium alginate has good viscosity and mechanical properties. The mechanical properties of the polyvinyl alcohol and sodium alginate mixed reinforced composite material are improved. The silane coupling agent promotes the interface bonding of polyethylene mixed cross-linked sodium alginate, improves the compatibility and bonding strength of the composite material, and improves the tensile strength, elastic modulus and toughness of the material. In the subsequent pressing process of the graphite material, it helps to make the various components of the graphite material bond tightly and press into a film.
[0031] Optionally, the thermal conductor is one or more of nano-scale silicon carbide, aluminum nitride, boron nitride, magnesium oxide, and aluminum oxide.
[0032] By adopting the above technical solution, the addition of thermal conductive agent can significantly improve the thermal conductivity of graphite material, so that it performs well in applications such as heat sinks and thermal management materials, and can transfer heat quickly and effectively; it can also improve the thermal stability of graphite material, so that it can still maintain good thermal conductivity at high temperatures, and is suitable for thermal management applications in high temperature environments.
[0033] Preferably, the plasticizer is one or more of diallyl phthalate, dioctyl phthalate, and dioctyl terephthalate.
[0034] By adopting the above technical solution, the plasticizer can reduce the melt viscosity of the graphite material, improve its fluidity and plasticity, make the graphite material easier to shape during the processing, increase the flexibility and elasticity of the material, make it less likely to suffer brittle fracture when subjected to external forces, and improve the impact resistance of the material.
[0035] Preferably, the thin film coating is a SiC coating, and the thickness of the coating is 20-30 μm.
[0036] By adopting the above technical scheme, the SiC coating improves the oxidation resistance of graphite materials in high-temperature oxidizing atmospheres, protects graphite materials from oxidation corrosion, and prolongs their service life; enhances the physical and mechanical properties of graphite materials, such as improving hardness, wear resistance and impact resistance, making them more durable when subjected to external forces; SiC coating can improve the stability of graphite materials in chemical environments, reduce corrosion and chemical reactions of graphite materials, and is suitable for application fields that require high chemical stability.
[0037] In a second aspect, the present application provides a method for preparing a heat dissipation graphite material for a large-screen LED display, comprising the following steps:
[0038] (1) grinding graphite powder, and then mixing with nano silver, modified nano carbon fiber, modified sodium alginate, sodium carboxymethyl cellulose, a thermal conductor and a plasticizer, stirring evenly, and pressing to obtain a film;
[0039] (2) The pressed film is baked in a nitrogen atmosphere at a temperature of 400-420° C., a film coating is applied to the baked film, and the film is cut to obtain a heat dissipation graphite material.
[0040] By adopting the above technical solution, various raw materials are mixed evenly in the early stage to increase the surface area and reaction activity of the materials, and the compactness and uniformity of the materials are ensured during the pressing process.
[0041] The pressed film is baked, the organic components in the material will volatilize, and the graphite particles will rearrange to form a more compact structure, thereby improving the thermal conductivity of the material. Then a thin film coating is applied to improve the wear resistance and corrosion resistance of the material.
[0042] In summary, this application has the following beneficial effects:
[0043] 1. The graphite powder in this application has high thermal conductivity, which can effectively improve the thermal conductivity of the heat dissipation graphite material, accelerate the transfer of heat, and thus improve the heat dissipation efficiency. The graphite powder has good chemical stability, mechanical strength and toughness, and the obtained heat dissipation graphite material has better comprehensive performance.
[0044] 2. The modified nano-carbon fiber in the present application has high thermal conductivity, can be dispersed in the graphite powder structure, adsorb graphite powder and nano-silver, so that the graphite powder, nano-silver and modified nano-carbon fiber are closely connected, forming a good heat conduction path, improving the thermal conductivity of the graphite material, and thus enhancing the heat dissipation effect.
[0045] 3. The modified sodium alginate in this application has a certain viscosity, so that the graphite powder, nanosilver and modified nanocarbon fibers are tightly bonded. The prepared graphite material can meet the high requirements of LED large-screen displays for heat dissipation performance. The material is widely used in the heat dissipation system of LED large-screen displays, effectively reducing the temperature of the LED large screen and improving the display effect and service life. DETAILED DESCRIPTION
[0046] Preparation example of modified carbon nanofiber
[0047] Preparation Example 1-1
[0048] The preparation method of modified carbon nanofiber comprises the following steps:
[0049] (1) 1.2 kg of carbon nanofibers were dispersed in 2 L of 20% sulfuric acid solution, soaked at 82 °C for 3 h, washed with water, and then mixed with 1 L of 95% ethanol solution and ball milled to obtain pretreated carbon nanofibers;
[0050] (2) dispersing the carbon nanofibers pretreated in step (1) in 1.8 L of deionized water, adding nano-nickel, and stirring to obtain a mixed solution;
[0051] (3) Spraying the acetic acid solution of chitosan on the surface of graphene, drying, then adding it to the mixed solution of step (2), stirring evenly, filtering, and drying to obtain modified nano-carbon fibers.
[0052] The acetic acid solution of chitosan is prepared by dispersing 0.5 kg of chitosan in 1 L of acetic acid solution with a mass fraction of 12% and stirring the mixture evenly.
[0053] The mass ratio of the acetic acid solution of nano-carbon fiber, nano-nickel, graphene and chitosan is 1g:0.2g:30mg:0.3mL.
[0054] Preparation Example 1-2
[0055] The difference from Preparation Example 1-1 is that in step (2), no nano nickel is added.
[0056] Preparation Example 1-3
[0057] The difference from Preparation Example 1-1 is that in step (3), graphene is not added.
[0058] Preparation Example 1-4
[0059] The difference from Preparation Example 1-1 is that in step (3), no acetic acid solution of chitosan is added.
[0060] Preparation Example 1-5
[0061] The difference from Preparation Example 1-1 is that the mass ratio of the acetic acid solution of nano-carbon fiber, nano-nickel, graphene and chitosan is 1g:0.5g:25mg:0.5mL.
[0062] Preparation Example 1-6
[0063] The difference from Preparation Example 1-1 is that the mass ratio of the acetic acid solution of nano-carbon fiber, nano-nickel, graphene and chitosan is 1 g:0.8 g:20 mg:0.7 mL.
[0064] Preparation example of modified sodium alginate
[0065] Preparation Example 2-1
[0066] The preparation method of modified sodium alginate comprises the following steps:
[0067] (1) 0.7 kg of sodium alginate was dispersed in 1 L of deionized water, the pH value was adjusted to 9 with a 25% by mass sodium hydroxide solution, 0.007 kg of triethylenediamine and 0.005 kg of toluene diisocyanate TDI were added, and the mixture was stirred at 75° C. for 1 h to obtain a cross-linked modified sodium alginate solution, 1 L of 95% by mass ethanol was added, the mixture was filtered, and the mixture was dried to obtain a sodium alginate powder;
[0068] (2) The sodium alginate powder of step (2) is dispersed in 1.2 L of deionized water, polyvinyl alcohol, silane coupling agent and copper powder are added, stirred evenly, dried and ground to obtain modified sodium alginate.
[0069] The mass ratio of sodium alginate, polyvinyl alcohol and silane coupling agent is 1:0.5:0.2.
[0070] Preparation Example 2-2
[0071] The difference from Preparation Example 2-1 is that in step (2), no polyvinyl alcohol is added.
[0072] Preparation Example 2-3
[0073] The difference from Preparation Example 2-1 is that in step (2), no silane coupling agent is added.
[0074] Preparation Example 2-4
[0075] The difference from Preparation Example 2-1 is that the mass ratio of sodium alginate, polyvinyl alcohol and silane coupling agent is 1:0.8:0.1.
[0076] Preparation Example 2-5
[0077] The difference from Preparation Example 2-1 is that the mass ratio of sodium alginate, polyvinyl alcohol and silane coupling agent is 1:0.2:0.6.
[0078] Example
[0079] Example 1
[0080] A heat dissipation graphite material for LED large-screen display comprises a graphene layer and a thin film coating. The graphene layer comprises the following raw materials: 60 kg of graphite powder, 1 kg of nano silver, 25 kg of modified nano carbon fiber, 15 kg of modified sodium alginate, 3 kg of sodium carboxymethyl cellulose, 8 kg of thermal conductor and 5 kg of plasticizer.
[0081] The thermal conductor is aluminum nitride and the plasticizer is diallyl phthalate.
[0082] The thin film coating is a SiC coating, and the thickness of the coating is 25 μm.
[0083] The method for preparing a heat dissipation graphite material for LED large-screen display comprises the following steps:
[0084] (1) pulverizing graphite powder, and then mixing it with nano silver, modified nano carbon fiber, modified sodium alginate, sodium carboxymethyl cellulose, a thermal conductor and a plasticizer, stirring evenly, and loading it into a mold of an isostatic press for isostatic pressing, the molding pressure is 200 MPa, the pressure holding time is 20 minutes, and a film with a thickness of 15 μm is obtained;
[0085] (2) The pressed film is baked in a nitrogen atmosphere at a temperature of 410° C. The film coating is adhered to the baked film with an epoxy acrylic resin adhesive and cut to obtain a heat dissipating graphite material.
[0086] The modified nano-carbon fiber was prepared according to Preparation Example 1-1, and the modified sodium alginate was prepared according to Preparation Example 2-1.
[0087] Example 2
[0088] A heat dissipation graphite material for LED large-screen display, which differs from Example 1 in that the graphene layer includes the following raw materials: 50 kg of graphite powder, 2 kg of nanosilver, 30 kg of modified nanocarbon fiber, 10 kg of modified sodium alginate, 6 kg of sodium carboxymethyl cellulose, 5 kg of thermal conductor and 3 kg of plasticizer.
[0089] Example 3
[0090] A heat dissipation graphite material for LED large-screen display, which differs from Example 1 in that the mass ratio of graphite powder, modified nano-carbon fiber and modified sodium alginate is 4:2:1.
[0091] Example 4
[0092] A heat dissipation graphite material for LED large-screen display, which differs from Example 1 in that the mass ratio of graphite powder, modified nano-carbon fiber and modified sodium alginate is 5:2.5:1.
[0093] Example 5
[0094] A heat dissipation graphite material for LED large-screen display, which differs from Example 1 in that the modified nano-carbon fiber adopts Preparation Example 1-2.
[0095] Example 6
[0096] A heat dissipation graphite material for LED large-screen display, which differs from Example 1 in that the modified nano-carbon fiber adopts Preparation Example 1-3.
[0097] Example 7
[0098] A heat dissipation graphite material for LED large-screen display, which differs from Example 1 in that the modified nano-carbon fiber adopts Preparation Example 1-4.
[0099] Example 8
[0100] A heat dissipation graphite material for LED large-screen display, which differs from Example 1 in that the modified nano-carbon fiber adopts Preparation Example 1-5.
[0101] Example 9
[0102] A heat dissipation graphite material for LED large-screen display, which differs from Example 1 in that the modified nano-carbon fiber adopts Preparation Example 1-6.
[0103] Example 10
[0104] A heat dissipation graphite material for LED large-screen display, which differs from Example 1 in that the modified sodium alginate adopts Preparation Example 2-2.
[0105] Embodiment 11
[0106] A heat dissipation graphite material for LED large-screen display, which differs from Example 1 in that the modified sodium alginate adopts Preparation Example 2-3.
[0107] Example 12
[0108] A heat dissipation graphite material for LED large-screen display, which differs from Example 1 in that the modified sodium alginate adopts Preparation Example 2-4.
[0109] Example 13
[0110] A heat dissipation graphite material for LED large-screen display, which differs from Example 1 in that the modified sodium alginate adopts Preparation Example 2-5.
[0111] Comparative Example
[0112] Comparative Example 1
[0113] A heat dissipation graphite material for LED large-screen display, which differs from Example 1 in that modified nano-carbon fibers are not added.
[0114] Comparative Example 2
[0115] A heat dissipation graphite material for LED large-screen display, which differs from Example 1 in that the modified nano-carbon fibers are replaced by an equal amount of nano-carbon fibers.
[0116] Comparative Example 3
[0117] A heat dissipation graphite material for LED large-screen display, which differs from Example 1 in that modified sodium alginate is not added.
[0118] Comparative Example 4
[0119] A heat dissipation graphite material for LED large-screen display, which differs from Example 1 in that an equal amount of sodium alginate is used to replace modified sodium alginate.
[0120] Performance testing
[0121] The heat dissipation graphite materials for LED large screen display prepared in Examples 1-13 and Comparative Examples 1-4 were subjected to performance tests;
[0122] The density test was conducted using the density tester WKT-3000E.
[0123] The tensile strength test refers to GB / T 21921-2008, and the tensile test is carried out using a universal experimental tensile machine with a tensile rate of 0.5mm / min;
[0124] The thermal conductivity test uses a thermal conductivity tester LFA447 to test the thermal conductivity of the sample in the horizontal and vertical directions respectively; the bending resistance test: fix one end of the sample, and then rotate the other end of the sample to make the sample rotate 90° back and forth on both sides. The rotation radius of the sample is 5 cm, and the rotation frequency is 1 second. The sample rotates 90° to one side and then 180° in the opposite direction, and then rotates 90° in the opposite direction to return to the starting position, which is recorded as one time. The number of rotations when the sample breaks is recorded. The test results are shown in Table 1.
[0125] Table 1 Test data of embodiments and comparative examples
[0126]
[0127] Combining the examples and the data in Table 1, it can be seen that the graphite materials prepared in Examples 1-2, Example 8 and Example 12 have good mechanical properties, thermal conductivity and bending resistance. Among them, the density of Example 1 is 1.91 g / cm 3 The tensile strength is 96.5MPa, the thermal conductivity in the horizontal direction is 1912W / m﹒K, the thermal conductivity in the vertical direction is 78.5W / m﹒K, and the bending resistance is 10746 times, indicating that the modified nano-carbon fiber of the present application has high thermal conductivity and can be dispersed in the graphite powder structure. The modified sodium alginate makes the graphite powder, nano-silver and modified nano-carbon fiber bond tightly, enhances the bonding and stability of the graphite material, and avoids cracking or deformation of the material.
[0128] Examples 3-4 further limit the mass ratio of graphite powder, modified nano-carbon fiber and modified sodium alginate. It can be seen from Table 1 that the density, tensile strength, horizontal thermal conductivity, vertical thermal conductivity and bending resistance of Examples 3-4 are all greater than those of Example 1, indicating that the graphite powder, modified nano-carbon fiber and modified sodium alginate have a synergistic effect, forming a good heat conduction path, improving the thermal conductivity of the graphite material, and thus enhancing the heat dissipation effect. The graphite material has excellent thermal conductivity, good wear resistance and corrosion resistance, and can meet the high requirements of LED large-screen displays for heat dissipation performance. The material is widely used in the heat dissipation system of LED large-screen displays, effectively reducing the temperature of the LED large screen, and improving the display effect and service life.
[0129] In the preparation method of modified nano-carbon fiber in Example 5, nano-nickel is not added. As shown in Table 1, the density is 1.82 g / cm 3 , tensile strength is 94.1MPa, horizontal thermal conductivity is 1902W / m﹒K, vertical thermal conductivity is 77.6W / m﹒K, and bending resistance is 10723 times, indicating that nano-nickel has high electrical conductivity and thermal conductivity. Nano-nickel is loaded in the pore structure and surface of nano-carbon fibers, which significantly improves the electrical conductivity and thermal conductivity of the material; it can also enhance the mechanical properties of nano-carbon fibers such as strength and toughness.
[0130] In the preparation method of modified carbon nanofiber in Example 6, graphene is not added. As shown in Table 1, the density is 1.73 g / cm 3 , tensile strength is 92.3MPa, horizontal thermal conductivity is 1890W / m﹒K, vertical thermal conductivity is 75.2W / m﹒K, and bending resistance is 10711 times, indicating that graphene has extremely high thermal conductivity, mechanical strength and folding resistance. Graphene and nano-carbon fibers are tightly bonded, which increases the thermal conductivity and mechanical strength of nano-carbon fibers. In the early mixing process of graphite materials, each component is mixed evenly to ensure the density and uniformity of the material.
[0131] In the preparation method of Example 7, no chitosan acetic acid solution is added in the modified nano-carbon fiber. As shown in Table 1, the density is 1.85 g / cm 3 , the tensile strength is 95.4MPa, the thermal conductivity in the horizontal direction is 1908W / m﹒K, the thermal conductivity in the vertical direction is 77.9W / m﹒K, and the bending resistance is 10731 times, indicating that chitosan is used as an adhesive, chitosan is coated with graphene, the mechanical properties of graphene are increased, and the graphene is stably loaded on the surface of nanocarbon fibers, which subsequently improves the corresponding properties of the material.
[0132] Example 9 changes the mass ratio of the acetic acid solution of nano-carbon fiber, nano-nickel, graphene and chitosan. It can be seen from Table 1 that the density, tensile strength, horizontal thermal conductivity, vertical thermal conductivity and bending resistance of Example 9 are all greater than those of Examples 5-7, but worse than those of Examples 1 and 8, indicating that nano-nickel is loaded in the pore structure and surface of nano-carbon fiber, and chitosan is coated with graphene, so that graphene is stably loaded on the surface of nano-carbon fiber. Chitosan is sticky, so that graphene and nano-carbon fiber are closely bonded, and at the same time, the structure of nano-carbon fiber, nano-nickel and graphene is dense, and then mixed with other components to improve the corresponding properties of graphite material.
[0133] In the preparation method of modified sodium alginate in Example 10, polyvinyl alcohol is not added. As shown in Table 1, the density is 1.83 g / cm 3 The tensile strength is 94.5MPa, the thermal conductivity in the horizontal direction is 1904W / m﹒K, the thermal conductivity in the vertical direction is 77.8W / m﹒K, and the bending resistance is 10730 times, indicating that polyvinyl alcohol has good film-forming and adhesion properties, and sodium alginate has biocompatibility and gel-forming ability. The mixture of the two enhances the mechanical properties such as strength and toughness of the composite material, and subsequently improves the density of the graphite material.
[0134] In the preparation method of Example 11, no silane coupling agent is added to the modified sodium alginate. As shown in Table 1, the density is 1.84 g / cm 3 The tensile strength is 94.6MPa, the thermal conductivity in the horizontal direction is 1906W / m﹒K, the thermal conductivity in the vertical direction is 77.9W / m﹒K, and the bending resistance is 10732 times, indicating that the silane coupling agent promotes the interface bonding of polyethylene mixed with cross-linked sodium alginate, improves the compatibility and bonding strength of the composite material, and improves the tensile strength, elastic modulus and toughness of the material. It will help to improve the corresponding properties of the graphite material in the future, help to mix the various components of the graphite material evenly, and help to press into a film.
[0135] Example 13 changes the mass ratio of sodium alginate, polyvinyl alcohol and silane coupling agent. It can be seen from Table 1 that the density, tensile strength, horizontal thermal conductivity, vertical thermal conductivity and bending resistance of Example 13 are greater than those of Example 10-11, but worse than those of Example 1 and Example 12, indicating that the mechanical properties of the polyvinyl alcohol and sodium alginate mixed reinforced composite material, the silane coupling agent promotes the interface bonding of polyethylene mixed and cross-linked sodium alginate, improves the compatibility and bonding strength of the composite material, and improves the tensile strength, elastic modulus and toughness of the material.
[0136] Comparative Example 1 does not add modified nanocarbon fibers. As shown in Table 1, the density is 1.53 g / cm 3The tensile strength is 71.3MPa, the thermal conductivity in the horizontal direction is 1723W / m﹒K, the thermal conductivity in the vertical direction is 53.2W / m﹒K, and the bending resistance is 10523 times, indicating that the modified nano-carbon fiber has high thermal conductivity, can be dispersed in the graphite powder structure, adsorb graphite powder and nano-silver, so that the graphite powder, nano-silver and modified nano-carbon fiber are closely connected, forming a good heat conduction path, improving the thermal conductivity of the graphite material, and thus enhancing the heat dissipation effect.
[0137] Comparative Example 3 does not add modified sodium alginate. From Table 1, it can be seen that the density is 1.62 g / cm 3 The tensile strength is 75.9MPa, the thermal conductivity in the horizontal direction is 1810W / m﹒K, the thermal conductivity in the vertical direction is 60.3W / m﹒K, and the bending resistance is 10627 times, indicating that the modified sodium alginate has a certain viscosity, which makes the graphite powder, nanosilver and modified nanocarbon fibers bond tightly to form a stable structure, which makes the graphite material have better mechanical properties and is not easy to break.
[0138] Comparative Example 2 and Comparative Example 4 respectively replace the modified nano-carbon fiber with an equal amount of nano-carbon fiber and replace the modified sodium alginate with an equal amount of sodium alginate. As can be seen from Table 1, the density, tensile strength, horizontal thermal conductivity, vertical thermal conductivity and bending resistance are all worse than those of Comparative Example 1 and Comparative Example 3, indicating that the modified nano-carbon fiber and sodium alginate in the present application have better comprehensive properties, and the corresponding properties of the graphite material are subsequently improved.
[0139] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. A heat dissipation graphite material for LED large screen display, comprising a graphene layer and a thin film coating, characterized in that: The graphene layer comprises the following raw materials: 50-60 parts of graphite powder, 1-2 parts of nano silver, 25-30 parts of modified nano carbon fiber, 10-15 parts of modified sodium alginate, 3-6 parts of sodium carboxymethyl cellulose, 5-8 parts of thermal conductor and 3-5 parts of plasticizer; The preparation method of the modified carbon nanofiber comprises the following steps: (1) 1.2 kg of carbon nanofibers were dispersed in 2 L of 20% sulfuric acid solution, soaked at 82 °C for 3 h, washed with water, and then mixed with 1 L of 95% 0039 ethanol solution and ball milled to obtain pretreated carbon nanofibers; (2) dispersing the carbon nanofibers pretreated in step (1) in 1.8 L of deionized water, adding nano-nickel, and stirring evenly to obtain a mixed solution; (3) Spraying the acetic acid solution of chitosan on the surface of graphene, drying, then adding the solution to the mixed solution of step (2), stirring evenly, filtering, and drying to obtain modified carbon nanofibers; The acetic acid solution of chitosan is prepared by dispersing 0.5 kg of chitosan in 1 L of acetic acid solution with a mass fraction of 12% and stirring evenly. The usage ratio of the acetic acid solution of the nano-carbon fiber, nano-nickel, graphene and chitosan is 1g:0.2-0.5g:25-30mg:0.3-0.5mL; The preparation method of the modified sodium alginate comprises the following steps: (1) Disperse 0.7 kg of sodium alginate in 1 L of deionized water, adjust the pH value to 9 with 25% by mass sodium hydroxide solution, add 0.007 kg of triethylenediamine and 0.005 kg of toluene diisocyanate TDI, stir at 75 °C for 1 h to obtain a cross-linked modified sodium alginate solution, add 1 L of 95% by mass ethanol, filter and dry to obtain sodium alginate powder; (2) dispersing the sodium alginate powder of step (1) in 1.2 L of deionized water, adding polyvinyl alcohol, silane coupling agent and copper powder, stirring evenly, drying and grinding to obtain modified sodium alginate; The mass ratio of the sodium alginate, polyvinyl alcohol and silane coupling agent is 1:0.5-0.8:0.1-0.
2.
2. A heat dissipation graphite material for LED large screen display according to claim 1, characterized in that: The mass ratio of the graphite powder, the modified carbon nanofiber and the modified sodium alginate is 4-5:2-2.5:
1.
3. The heat dissipation graphite material for LED large screen display according to claim 1, characterized in that: The thermal conductor is one or more of nano-scale silicon carbide, aluminum nitride, boron nitride, magnesium oxide, and aluminum oxide.
4. The heat dissipation graphite material for LED large screen display according to claim 1, characterized in that: The plasticizer is one or more of diallyl phthalate, dioctyl phthalate and dioctyl terephthalate.
5. The heat dissipation graphite material for LED large screen display according to claim 1, characterized in that: The thin film coating is a SiC coating, and the thickness of the coating is 20-30 μm.
6. The method for preparing a heat dissipation graphite material for LED large screen display according to claim 1, characterized in that: The steps include: (1) pulverizing graphite powder, and then mixing it with nano silver, modified nano carbon fiber, modified sodium alginate, sodium carboxymethyl cellulose, a thermal conductor and a plasticizer, stirring evenly, and pressing to obtain a film; (2) The pressed film is baked in a nitrogen atmosphere at a temperature of 400-420° C., a film coating is applied to the baked film, and the film is cut to obtain a heat dissipating graphite material.
Citation Information
Patent Citations
Method for preparing graphene by reduction of sulfur-contained compound
CN101987729A
Graphene-modified heat conduction film
CN103738940A